can anyone explain me the solution pls???
Attachments:
![](https://hi-static.z-dn.net/files/d1c/7f2128eb1855ace6d044c3348bf19924.jpg)
Answers
Answered by
4
Hello Mate!
So, here we have to factorise.
x² + 4y² - z² - 4xy
Now, obviously what to do next. Many would try for a² - b² formula but focus that - 4xy is given too. So, we will use a² + b² - 2ab = ( a - b )² formula.
= x² + (2y)² - 2×x×2y - z²
= ( x - 2y )² - z²
Now using a² - b² = ( a + b )( a - b ) we get
= ( x - 2y - z )( x - 2y + z )
"Have great future ahead!"
So, here we have to factorise.
x² + 4y² - z² - 4xy
Now, obviously what to do next. Many would try for a² - b² formula but focus that - 4xy is given too. So, we will use a² + b² - 2ab = ( a - b )² formula.
= x² + (2y)² - 2×x×2y - z²
= ( x - 2y )² - z²
Now using a² - b² = ( a + b )( a - b ) we get
= ( x - 2y - z )( x - 2y + z )
"Have great future ahead!"
ShuchiRecites:
Thanks for attempting brainliest sis
Answered by
1
hey
____________________
using two identities
(a-b)^2=a^2+b^2-2ab
(a)^2-(b)^2 = (a+b)(a-b)
for the full solution refer to the attachment
hope helped
_____________________
____________________
using two identities
(a-b)^2=a^2+b^2-2ab
(a)^2-(b)^2 = (a+b)(a-b)
for the full solution refer to the attachment
hope helped
_____________________
Attachments:
![](https://hi-static.z-dn.net/files/da8/73dae145592fc8a551d4f2e45f0993a8.jpg)
Similar questions